NARRATIVES OF MERITOCRACY IN EDUCATION AND THE REPRODUCTION OF SOCIAL INEQUALITY: A LITERATURE REVIEW IN A CRITICAL SOCIOLOGICAL PERSPECTIVE: NARASI MERITOKRASI DALAM PENDIDIKAN DAN REPRODUKSI KETIMPANGAN SOSIAL: TINJAUAN LITERATUR DALAM PERSPEKTIF SOSIOLOGI KRITIS - Adit Mohammad Aziz; Minarni Manoppo; Hariyanto; Oman Sukmana (SOSIOEDUKASI, 2025)
This study aims to examine how the narrative of meritocracy in education contributes to the reproduction of social inequality through a critical sociological approach. Education is often assumed to be a means of social mobility based on individual ability and effort, but the literature shows that this system is fraught with structural biases. This study uses a systematic literature review method with a critical qualitative approach. Data sources come from scientific articles, academic books, policy reports, and educational documents collected from databases such as Google Scholar, Scopus, and DOAJ. The selected literature focuses on meritocracy, educational inequality, as well as critical theories of education such as cultural capital, habitus, and symbolic dominance. The analysis was carried out thematically and interpretively. The results of the study show that the education system actually strengthens social stratification through evaluation and selection mechanisms that appear to be neutral. The ideology of meritocracy plays a role in justifying inequality and blaming individuals for their failures. This study concludes that a socially just approach to education needs to be developed to break symbolic dominance and open up space for more inclusive and equitable policies